2000
DOI: 10.1007/pl00001115
|View full text |Cite
|
Sign up to set email alerts
|

Faulting Processes of Historic (1917–1962) M≥ 6.0 Earthquakes Along the North-central Caribbean Margin

Abstract: The plate boundary along the north-central Caribbean margin is geologically complex. Our understanding of this complexity is hampered by the fact that plate motions are relatively slow (1 to 2 cm/yr), so that recent seismicity often does not provide a complete picture of tectonic deformation. Studies of the faulting processes of instrumentally recorded earthquakes occurring prior to 1962 thus provide important information regarding the nature and rate of seismic deformation within the region, and are essential… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
21
0
1

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 22 publications
1
21
0
1
Order By: Relevance
“…It has been suggested that most of the stress accumulated by the Caribbean–North American plate motion is released seismically along the northern Cuban margin during a relatively few but strong earthquakes (Perrot et al 1997; Van Dusen & Doser 2000). This sparse occurrence of strong and moderate earthquakes makes it difficult to use earthquake focal mechanisms for mapping the crustal stress field in this area.…”
Section: The Tectonic Regime Of the Areamentioning
confidence: 99%
“…It has been suggested that most of the stress accumulated by the Caribbean–North American plate motion is released seismically along the northern Cuban margin during a relatively few but strong earthquakes (Perrot et al 1997; Van Dusen & Doser 2000). This sparse occurrence of strong and moderate earthquakes makes it difficult to use earthquake focal mechanisms for mapping the crustal stress field in this area.…”
Section: The Tectonic Regime Of the Areamentioning
confidence: 99%
“…At the northeastern edge of the study area (Figure ), the Oriente fault bounds the Cayman trough, a 45–50 Ma oceanic pull apart basin [ Rosencrantz et al , ], to the north. Earthquake focal mechanisms show pure left‐lateral strike‐slip motion from the mid‐Cayman spreading center to the southern Cuban margin [ Perrot et al , ] where the fault trace slightly changes direction to become transpressional [ Calais and de Lepinay , ], with earthquake focal mechanisms showing a combination of thrust and strike‐slip faulting [ Van Dusen and Doser , ]. To the east, the Oriente fault pursues its course through the Windward Passage, along the northern Haitian coast as the “Septentrional fault” [ Calais and de Lépinay , ], then farther east on land through the Cibao Valley of the Dominican Republic [ Calais and de Lépinay , ] where paleoseimological studies indicate a Holocene slip rate of 9±3 mm/yr [ Prentice et al , ], in agreement with GPS estimates [ Calais et al , ].…”
Section: Introductionmentioning
confidence: 99%
“…1) whose historic record of earthquakes dates back more than 300 yr. Most notable are: the 1692 Port Royal earthquake whose magnitude could have been as high as 8 (Clarke 1995); the 1907 Kingston earthquake whose magnitude was Ms 6.5 (Pereira 1977); and the 1957 Montego Bay event with a recalculated magnitude of Mw 6.9 (Van Dusen & Doser 2000). The epicentre of the 1957 event was relocated from an initial offshore locality to fall on land in NW Jamaica (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…The polar plot shows stress regime in the area outlined by dashes: diamond =σ 1 = azimuth 254°/plunge 16°; circle =σ 2 = 348°/12°; triangle =σ 3 = 113°/70°, where σ 1 is the maximum compressive stress (Moreno et al 2002). Fault plane solutions A—G with pressure axes (dots) and slip directions (small arrows) are based on waveform modelling (Van Dusen & Doser 2000); I and H are Harvard CMT fault plane solutions for recent moderate (Mw 5.5) Jamaica earthquakes of 1988 Novermber 12 and 1993 January 13, respectively. Arrows with accompanying numbers are estimates of slip in mm yr −1 from GPS measurements given for the Caribbean Plate interior and tangential and normal to the OFZ near southeastern Cuba (De Mets et al 2000) and for Hispaniola (Mann et al 2002).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation